Sleep difficulties, incident dementia and all‐cause mortality among older adults across 8 years: Findings from the National Health and Aging Trends Study. (2nd June 2021) - Robbins, Rebecca; Weaver, Matthew D.; Barger, Laura K.; Wang, Wei; Quan, Stuart F.; Czeisler, Charles A.
Summary: Sleep difficulties have been implicated in the development and progression of dementia and in all‐cause mortality. This study examines the relationship between sleep difficulties, incident dementia and all‐cause mortality over 8 years of follow‐up among a nationally representative sample of older (≥65 years) adults in the United States. We used data collected from the National Health and Aging Trends Study (NHATS) from 2011 to 2018, a prospective cohort study of Medicare beneficiaries. At baseline, the NHATS sample comprised 6, 376 older adults who were representative of 32 million older adults. Respondents reported routine difficulty initiating sleep or difficulty falling back asleep "most nights" or "every night" in each study year. In each year, dementia was determined by either self‐reported diagnosis or performance on immediate and delayed recall word and clock drawing tests, whereas all‐cause mortality was determined by proxy. We conducted Cox proportional hazards modelling, adjusting for age, sex, marital status and chronic conditions. In models predicting all‐cause mortality, we also controlled for dementia. Among respondents at baseline, 19% were 65–75 years of age, 71% identified as non‐Hispanic white and 59% were female. Difficulty initiating sleep (hazard ratio [HR], 1.49; 95% confidence interval [CI], 1.25–1.77), difficulty falling back asleep (HR,  = 1.39; 95% CI, 1.14–1.70) and concurrent sleep difficulties (HR,  1.58; 95% CI, 1.25–1.99) were associated with greater risk of dementia. Difficulty initiating sleep (HR,  1.44; 95% CI, 1.20–1.72), difficulty falling back asleep (HR,  1.56; 95% CI, 1.29–1.89), and concurrent sleep difficulties (HR,  1.80; 95% CI, 1.44–2.24) were associated with greater risk of all‐cause mortality. Our findings demonstrate that reported difficulties are prospectively associated with an increased risk of dementia and all‐cause mortality among older people.